Nursing management actions during the new corona virus pandemic (Research, Society and Development, 2022)
Nurses play a leading role in the construction of the care system, as they are able to interact widely with all health professionals, developing fundamental actions for health promotion/recovery. The objective of which is to analyze the managerial instruments used in the professional practice of nurses in times of a pandemic, in the sectors of service to Covid-19. This is an exploratory, descriptive study with a qualitative approach. The population consisted of 22 professionals who are part of the nursing team, who develop their activities in the public and private health institution. To carry out the data collection, an interview instrument was used containing open and closed questions, through google forms. The closed questions took into account the following variables of characterization of the subjects: sex, age, marital status, level of education, whereas the open questions dealt with the subject under study. For data collection, the methodological technique Snowball (“Snowball”) was used. Data collection took place between December 2021 and April 2022. Data analysis followed the Thematic Analysis proposed by Bardin. There were five thematic axes that describe: the strategies used for the distribution of the nursing team; management tools; the feelings experienced by nursing professionals and the turnover of nursing staff during the pandemic period and the difficulties experienced during the pandemic. The management of the nursing service on the front line of care has experienced moments of anguish, fear, turnover of nursing staff, change in the service scale.